Microbial Resources and Enological Significance: Opportunities and Benefits - Petruzzi, Leonardo; Capozzi, Vittorio; Berbegal, Carmen; Corbo, Maria R.; Bevilacqua, Antonio; Spano, Giuseppe; Sinigaglia, Milena (Frontiers in Microbiology, 2017)
Among the innovative trends in the wine sector, the continuous exploration of enological properties associated with wine microbial resources represents a cornerstone driver of quality improvement. Since the advent of starter cultures technology, the attention has been focused on intraspecific biodiversity within the primary species responsible for alcoholic fermentation (Saccharomyces cerevisiae) and, subsequently, for the so-called ‘malolactic fermentation’ (Oenococcus oeni). However, in the last decade, a relevant number of studies proposed the enological exploitation of an increasing number of species (e.g. non-Saccharomyces yeasts) associated with spontaneous fermentation in wine. These new species/strains may provide technological solutions to specific problems and/or improve sensory characteristics, such as complexity, mouth-feel and ﬂavours. This review offers an overview of the available information on the enological/protechnological significance of microbial resources associated with winemaking, summarizing the opportunities and the benefits associated with the enological exploitation of this microbial potential. We discuss proposed solutions to improve quality and safety of wines (e.g alternative starter cultures, multistrains starter cultures) and future perspectives.